The impact of circuit training among volleyball and basketball players girls in Tirana of Albania - Lleshi, Enkeleida; Mema, Blerina; Martiri, Altin; Lile, Anduela (Edelweiss Applied Science and Technology, 2024)
The study aims to evaluate the impact of a circuit training program on certain physical components in girls who play basketball and volleyball in Tirana of Albania. Speed and dexterity are considered essential components in sports games that should be practiced from an early age. Materials & Methods: The study involved 60 girls players (29 basketball players and 31 volleyball players) aged 13-14. The participants were assessed for body height, body weight, and body mass for each sport and underwent tests before and after the intervention including tests; SJ, CMJ, DJ 20cm, hexagon, shuttle run test 10x5m, T-Test and Lateral Change Direction. The groups followed circuit training for 15 minutes, three times a week for 11 weeks. Results: For the results of the study we used analysis of variance (ANOVA) with repeated measurements, was used to compare the improvement level of training circuit, which showed a statistically significant difference in the impact of the intervention on both groups. The significance level was taken as 0.05 in the comparisons (p< 0.05). Conclusions: The results of this paper were very encouraging and demonstrated the benefits on components of speed and agility for volleyball and basketball girl’s players after the training circuit. This training method showed that it should be implemented from a young age and throughout the season in these sports.